Accidents in situations with large stability values - Krüger, Stefan; Steinbach, Christoph; Rox, Nicolas; Kaufmann, Jörg; John, Ferenc (Volume 6: Ocean Engineering, 2011)
In the last two years a number of accidents with several dead or heavily injured crew members have been reported to the German Federal Bureau of Maritime Casualty Investigation caused by excessive roll motions with large transversal accelerations. All accidents happened on board of container vessels in situations of large stability and partial draft like in ballast or in laidup situations. Also the accident situations were similar in all cases. During harsh weather conditions the crew tried to keep the ship against the incoming sea at constant slow speed. It was possible to reconstruct the accident events and the occurrence of high transversal acceleration values by numerical seakeeping simulations. To figure out if container vessels have an inherent danger of such problems a numerical study on a group of fifteen container vessels of different sizes was carried out in the mentioned accident situations. In this paper the reported accidents and the numerical investigation on the accidents are described, furthermore the results of the extended numerical study are presented and a phenomenological conclusion is drawn from the results.